Effect of meditation on premenstrual syndrome in female medical students - Kaur, Harminder; Kaur, Nimarpreet; Akula, Gangadhar Reddy; Kodidala, Satyanath Reddy (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. A symptom complex of cyclic irritability, depression and lethargy is known as the premenstrual syndrome (PMS). Since ages women suffered from PMS. As varied as the etiology, innumerable treatment modalities have been put forward for PMS. Stress is accompanied most closely associated in PMS. Practicing yoga and meditation significantly important for PMS symptoms in reducing its symptoms and period crams as well. The present study aims the impact of meditation in people with PMS. The aim of the study was to see any effect of Shavasana (meditation) training on stress parameters in premenstrual syndrome in female medical students. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The present study was approved by institutional ethical committee. Thirty clinically healthy female medical students who were suffering from PMS selected using a premenstrual questionnaire. The values of heart rate, systolic and diastolic blood pressure, and serum cortisol were measured before meditation. Subjects were then taken through Shavasana (meditation) session for 4 weeks at the same time daily. On the last day of meditation session all above parameters were again recorded and the data was analyzed statistically. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The baseline values of all parameters in premeditation session compared to post meditation session. The basal SBP, DBP and HR of female medical students with PMS were significantly higher in pre meditation session than post meditation session with p value of SBP=0.0002, DBP=0.0001, HR<0.0001 respectively which indicated the presence of stress. Following a 4weeks of Shavasana meditation a significant fall in baseline SBP, DBP, HR and the serum cortisol value was observed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. These findings proves that Shavasana is an effective treatment modality to get rid of stress during premenstrual phase.